Genome-wide expression-monitoring of jasmonate-responsive genes of Arabidopsis using cDNA arrays. (December 2000) - Sasaki, Y.; Asamizu, E.; Shibata, D.; Nakamura, Y.; Kaneko, T.; Awai, K.; Masuda, T.; Shimada, H.; Takamiya, K-i.; Tabata, S.; Ohta, H.
Abstract : Jasmonates are generally considered to mediate signalling, such as defence responses, flowering and senescence. However, factors involved in the jasmonate signal-transduction pathway remain unclear. To clarify the functions and signalling mechanisms of jasmonates on a genome-wide level, we adopted a cDNA macroarray technique. We prepared nylon filters of a cDNA macroarray on which 2880 independent expressed sequence tag clones of Arabidopsis were blotted, and hybridized 33 P-labelled single-strand DNAs synthesized from mRNAs of methyl jasmonate (MeJA)- treated and untreated Arabidopsis plants to the nylon filters. By analysing the data from the cDNA macroarray, we identified many function-known and unknown genes as MeJA-responsive genes, and confirmed that the profiles of the expression showed good agreement with Northernblot analysis. These results demonstrate the efficiency of the cDNA macroarray for systematically analysing jasmonate-responsive genes on a genome-wide scale.